Quantifying the sensitivity of feedstock properties and process conditions on hydrochar yield, carbon content, and energy content. (August 2018) - Li, Liang; Wang, Yiying; Xu, Jiting; Flora, Joseph R.V.; Hoque, Shamia; Berge, Nicole D.
Highlights: Hydrothermal carbonization data were collected from the literature. Regression techniques were used to build statistical models. Random forest models fit data better than other models. Most influential parameters on hydrochar characteristics were determined. Importance of model parameters on hydrochar properties change with process conditions. Abstract: Hydrothermal carbonization (HTC) is a wet, low temperature thermal conversion process that continues to gain attention for the generation of hydrochar. The importance of specific process conditions and feedstock properties on hydrochar characteristics is not well understood. To evaluate this, linear and non-linear models were developed to describe hydrochar characteristics based on data collected from HTC-related literature. A Sobol analysis was subsequently conducted to identify parameters that most influence hydrochar characteristics. Results from this analysis indicate that for each investigated hydrochar property, the model fit and predictive capability associated with the random forest models is superior to both the linear and regression tree models. Based on results from the Sobol analysis, the feedstock properties and process conditions most influential on hydrochar yield, carbon content, and energy content were identified. In addition, a variational process parameter sensitivity analysis was conducted to determine how feedstock property importance changes with process conditions.